Costa Rica´s enhanced 2020 Nationally Determined Contribution (NDC) developed using CCAFS online participatory future scenario approach - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
The Ministry of Environment and Energy (MINAE) used CCAFS's future scenarios methodology to enhance the country's NDC. University for International Cooperation (UCI) designed and facilitated an online participatory consultation and over 350 stakeholders participated to develop sets of future scenarios based on contextual uncertainties that could positively or negatively influence Costa Rica´s ability to reach climate goals. These scenarios were used in all NDC sectors to discuss and improve the country's plans to reduce emissions and increase climate change resilience.